The Common Agricultural Policy of the European Community : Principles and Consequences: Occa Paper No.62. (Occasional Papers; Occasional Paper, 1988)
This chapter discusses principles and consequences of the common agricultural policy (CAP) of the European Community (EC). It shows that agricultural pricing policies aimed at supporting farm incomes were already in place in EC member countries before the inception of the CAP; indeed, in the presence of these policies, the CAP was a logical consequence of the extension of the common market to the agricultural sector. Thus, the flaws of the CAP can be traced back to national policies and attitudes toward agriculture. Recognition of the burden of agricultural support on the rest of the economy, as well as the growing budgetary costs, has elicited a greater public interest in the CAP. Equally, the trade frictions caused by export subsidies have underlined the CAP's international implications. For these reasons, the member states appear more determined than hitherto to bring agricultural expenditure under control. Given the wider effects of the CAP both on EC economies and the international community, it is to be hoped that current efforts at reform will be successful.